Penggunaan Instagram kursus @_arab_alazhar Sebagai Media Arabic Self-Directed Learning Mahasiswa Bahasa Arab - Alfalah, Adib; Maman Abdurrahman; Syihabuddin (Shaut al Arabiyyah, 2024)
This research aims to open new Instagram innovations as a medium for learning Arabic, especially self-directed learning. Instagram, which so far is only popular for posting photos or videos, is very effectively used as a medium for learning Arabic, and can increase students' self-learning motivation. Researchers focused on using the Instagram account @kursus_arab_alazhar as a favorite channel with the most followers, namely around 130 thousand followers. This research method uses a descriptive qualitative approach. Data collection uses triangulation techniques, through observation, interviews and documentation. While the analysis of research data refers to the Miles and Huberman model, namely through the stages of data reduction, data presentation, and conclusions. The results of the study show that the Instagram account @kursus_arab_alazhar is very interesting and effective as a medium for learning Arabic based on Self-Directed Learning. Arabic students gave a positive response that Instagram @kursus_arab_alazhar was able to increase self-learning motivation in learning Arabic and was recommended to be implemented as a medium for self-learning Arabic.